Identification of inhibitory immune checkpoints and relevant regulatory pathways in breast cancer stem cells. (1st May 2021) - Shi, Haojun; Yang, Yisi
Abstract: Immune checkpoint blockade (ICB) has become one of the most promising approaches to activating antitumor immunity. However, only a small subset of patients with breast cancer benefit from ICB treatment. To improve the therapeutic effect in the clinic, precision immunotherapy is proposed to accurately eliminate cancer stem cells that contribute to local recurrence or metastasis, but currently little is known about their immunological properties. In this study, breast cancer–specific datasets in The Cancer Genome Atlas were collected and analyzed by using multiple open‐access web servers. We found that the immunophenotype of breast cancer was characterized by a hypoactive immune microenvironment and a low response to immune checkpoint blockade. The innate immune checkpoint CD200 and the adaptive immune checkpoint CD276, respectively, exhibited a strong correlation with basal/stem gene signature and invasiveness gene signature, both of which represent breast cancer stem cells. Wnt, TGF‐β, and Hedgehog signaling, which are recognized as stemness‐related pathways, showed a significant association with the expression of CD200 and CD276, suggesting cancer stem cell–specific immune checkpoints could be downregulated by inhibiting these pathways. Of note, levels of CD200 and CD276 expression were higher in TGF‐β dominant breast cancer than in other immune types of breast cancer. We also identified gene signatures that represent Wnt, TGF‐β, and Hedgehog signaling‐related CD200 and CD276 expression in breast cancer stem cells. For the luminal A subtype, the patient group with a high level of these gene signatures plus a low infiltration of CD8 + T cells, or dendritic cells, or M1 macrophages had poor overall survival. Our study suggested that CD200 and CD276 are candidate inhibitory immune checkpoints in breast cancer stem cells, which are potentially regulated by Wnt, TGF‐β, and Hedgehog signaling. Synergistic inhibition of these stemness‐related pathways may improve the efficacy of ICB treatment targeting breast cancer stem cells in precision immunotherapy. Abstract : CD200 and CD276 are candidate inhibitory immune checkpoints in breast cancer stem cells, which are potentially regulated by Wnt, TGF‐β, and Hedgehog signaling. Synergistic inhibition of these stemness‐related pathways may improve the efficacy of ICB treatment targeting breast cancer stem cells in precision immunotherapy.